The Red Fish in a Shoal of Greenish‐Blue Fish? A Critique of the Biomedical Model of Autism Spectrum Disorder. Issue 4 (23rd November 2021) - Leysen, Joyce; Jacobs, Delphine; Ramaekers, Stefan
Abstract : The biomedical model states that autism is a neurodevelopmental disorder, called autism spectrum disorder (ASD). In this article, Joyce Leysen, Delphine Jacobs, and Stefan Ramaekers argue that this is a narrow way of looking at autism and, further, that the biomedical view has implications for our understanding of parenthood and circumscribes the pedagogical agency of parents of children diagnosed with ASD. The authors adopt a critical stance toward assumptions implicit in the biomedical model concerning autism, reject the model's status as a norm, and problematize the demands the biomedical approach places on parents. As both the object of analysis and an illustration of their argument, Leysen, Jacobs, and Ramaekers use an example of neurodiscourse that introduces the biomedical model of ASD on the public stage to a broad audience. Then, they propose that Martin Buber's thoughts on continual beginning anew, the dialogical nature of the parent–child relationship, and the importance of attention to the whole human being can provide a means to open up the currently narrow confines of the biomedical perspective on autism. Finally, the authors use Buber's concepts to articulate a pedagogical view on the parent–child relationship that restores parents' pedagogical agency.